Assessment of tumor antigen-loaded solid lipid nanoparticles as an efficient delivery system for dendritic cell engineering. (July 2013) - Bhargava, Arpit; Mishra, Dinesh; Khan, Saba; Varshney, Subodh K; Banerjee, Smita; Mishra, Pradyumna K
Aim: The work attempts to overcome tumor-associated immune tolerance using a surface-modified solid lipid nanoparticle (SLNP) delivery system for dendritic cell (DC) immunotherapy.Materials & methods: Different formulations of SLNPs (SLNPs-alone, cationic SLNPs and mannosylated SLNPs) were prepared using tumor cell lysates. Prepared nanoparticles were characterized and their ability to activate DCs to induce a tumor cell-specific response was assessed.Results: SLNPs induced a strong phagocytic signal to DCs without any significant toxicity. Comparatively, mannosylated SLNPs evoked an optimum and effective cell-mediated immune response with no significant toxicity.Conclusion: Surface-modified SLNPs may play a pivotal role in designing a clinically translatable DC-based immunotherapy for gastrointestinal malignancies. This novel approach may also facilitate the treatment of residual disease, following standard therapy. Original submitted 9 February 2012; Revised submitted 19 August 2012; Published online 14 January 2013